2017
DOI: 10.21272/sec.1(2).5-18.2017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of “policy paradigms” on energy security issues in protracted conflict environments: the case of Cyprus

Abstract: The research question that this article attempts to address is: what are the main policy paradigms that guide the opinion leaders throughout energy security matters within protracted conflict environments? Using the de facto divided island of Cyprus as our single case study, we will deliberately follow grounded theory in order to create conceptual definitions out of rudimentary "working ideas" that involve "protracted conflict environment", "energy security" and stakes in "decision making". This research enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Scientists [67][68][69][70][71][72][73][74][75][76] have confirmed that macroeconomic indicators influence a country's energy security and energy efficiency. Simultaneously, human capital and financial development have influenced CO 2 emissions and energy efficiency [67,68,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Malinauskaite et al [87] confirmed that energy efficiency of the industry sector has influenced the achievement of the goals of the Green Deal Policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientists [67][68][69][70][71][72][73][74][75][76] have confirmed that macroeconomic indicators influence a country's energy security and energy efficiency. Simultaneously, human capital and financial development have influenced CO 2 emissions and energy efficiency [67,68,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Malinauskaite et al [87] confirmed that energy efficiency of the industry sector has influenced the achievement of the goals of the Green Deal Policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the study results, the dependence of the level of GDP on energy efficiency and energy consumption was established. It is also worth noting the study (He, 2019;Mačaitytė, Virbašiūtė, 2018;Karakasis, 2017), which provides generalized arguments and counterarguments on the impact of institutional factors on the environment and the level of energy security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent events in the world have proven that energy security is among the most important guarantees of economic security. That is why the formation of a national policy in the field of energy and environmental protection should consider the priorities of energy security [7].…”
Section: Introductionmentioning
confidence: 99%